2002
DOI: 10.1074/jbc.m201233200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Chk1 Inhibition by UCN-01

Abstract: Chk1 is a serine-threonine kinase that plays an important role in the DNA damage response, including G 2 /M cell cycle control. UCN-01 (7-hydroxystaurosporine), currently in clinical trials, has recently been shown to be a potent Chk1 inhibitor that abrogates the G 2 /M checkpoint induced by DNA-damaging agents. To understand the structural basis of Chk1 inhibition by UCN-01, we determined the crystal structure of the Chk1 kinase domain in complex with UCN-01. Chk1 structures with staurosporine and its analog … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
129
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(135 citation statements)
references
References 21 publications
4
129
0
2
Order By: Relevance
“…Since part of the activation loop is interacting with a symmetry-related molecule in the crystal, it is impossible to determine from this structure whether the loop was in an apparently active conformation in solution prior to crystal packing or whether crystal packing induced the observed conformation. However, a similar conformation of the nonphosphorylated activation loop is observed in the crystal structure of the Chk1-staurosporine complex (33). There is a strong correlation between the phosphorylation of full-length ZAP-70 and its activation (3, 7, 11, 21, 22, 34 -36).…”
Section: Resultsmentioning
confidence: 65%
“…Since part of the activation loop is interacting with a symmetry-related molecule in the crystal, it is impossible to determine from this structure whether the loop was in an apparently active conformation in solution prior to crystal packing or whether crystal packing induced the observed conformation. However, a similar conformation of the nonphosphorylated activation loop is observed in the crystal structure of the Chk1-staurosporine complex (33). There is a strong correlation between the phosphorylation of full-length ZAP-70 and its activation (3, 7, 11, 21, 22, 34 -36).…”
Section: Resultsmentioning
confidence: 65%
“…Others have reported that UCN-01 inhibited cdks resulting in cell cycle arrest or apoptosis (De Azevedo et al 1996;Brusselbach et al 1998;Gersher 2000;Kohn et al 2002;Senderowicz 2002;Zhao et al 2002). In colon cancer, UCN-01 was shown to inhibit p53 up-regulation, chk2 and chk1, although the action of UCN-01 was determined to be independent of p53 (Yu et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For example, UCN-01 was first identified as protein kinase C (PKC) inhibitor but later found to inhibit both Chk1 and Chk2. 35,36 Caffeine, on the other hand, can inhibit ATM/ATR, which are upstream regulators of Chk1 and Chk2 kinases. 37,38 Here, we have used an RNA interference (RNAi)-mediated gene knockdown approach to investigate the comparative roles of Wee1, Chk1, and Myt1 kinases in the G 2 checkpoint pathway in Hela versus normal human mammary epithelial cells (HMEC), which lack or express functional p53 alleles, respectively.…”
Section: © 2 0 0 4 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%